2006
DOI: 10.1265/ehpm.11.115
|View full text |Cite
|
Sign up to set email alerts
|

Personal features and dropout from diabetic care

Abstract: Objective: To investigate the personal features associated with dropout from regular outpatient care among persons with type 2 diabetes mellitus (DM).Methods: A total of 160 DM patients were enrolled in the study. As a retrospective analysis, outpatient's clinical characteristics, lifestyle, or social features were gathered from their medical records or interview sheets. All the subjects were divided into two groups by adherence to diabetic care, namely, 'dropout case' (DC) or 'ongoing case' (OC), and were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 22 publications
3
51
1
Order By: Relevance
“…In contrast to our findings, Masuda et al found defaulters were younger, less likely to be on medications, had shorter duration of diabetes, and lower HbA1c levels [23]. The authors concluded that these patients with “milder” disease may have been discharging themselves from clinic due to the belief that their disease was not severe enough to warrant intensive therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Masuda et al found defaulters were younger, less likely to be on medications, had shorter duration of diabetes, and lower HbA1c levels [23]. The authors concluded that these patients with “milder” disease may have been discharging themselves from clinic due to the belief that their disease was not severe enough to warrant intensive therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Side effects play an important role in the choice of a pharmacological treatment. In addition, adverse drug-related reactions are frequently cited by patients as a reason for discontinuation of prescribed treatments such as antidepressants, [33] antidiabetic, [34] and antihypertensive medications. [35] The adverse event profiles of the first-generation PDE5is are generally similar.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Clearly, preventing dropout is crucial in managing diabetes, and several studies have analyzed the predictors of dropout and reasons for dropout 5,7,8,[12][13][14][15][16][17] . Reported predictors included young age, being employed, not taking medication, poor glycemic control, having high blood pressure and smoking 5,7,8,[12][13][14] . The common reasons for dropout include conflicts with work, low perceived concern for the disease, lack of perceived necessity and financial issues 8,15 .…”
Section: Introductionmentioning
confidence: 99%